Risk Management in Smallholder Cattle Production in Sekaran Village, Bojonegoro - Eko Ruddy Cahyadi; Mokhamad Syaefudin Andrianto; Surahman Surahman (Faculty of Animal Science, Universitas Gadjah Mada, 2019)
This study analyzes risks in smallholder cattle production. A household survey was carried out among 109 farmers in a village of Sekaran, one of cattle production center in Bojonegoro, East Java. The monthly average income of farmer household was Rp. 293,877 per capita and it has 2-3 cattles on average. A risk matrix was applied to plot 17 risks related to cattle and farmer households into four quadrants based on the occurrence probability and severity level. Drought, feed scarcity, cattle diseases, and farmer sickness had “high probability and severity level”, and therefore were prioritized to be addressed. The logit regression model of feed scarcity, cattle diseases showed that economies of scale significantly reduced risk of feed scarcity but it could increase risk of cattle diseases. Risk of cattle diseases could be reduced significantly by applying more intensive hygiene and treatment. A livestock pattern transformation from individually separated cages under individual farmers into an integrated or colony farm under farmer group is suggested as a risk management strategy in order to achieve economies of scale and effectively control livestock hygiene and treatment.